Mechanisms Of Ionizing Radiation Influences To Biological Cells (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
Article says about developing of atomic energetic, chain reaction processes in nuclear reactors, ways of maintaining of them, especially ionizing radiation influences to biological cells and biological changes. It shows that as a result influences to biological cells in an organism happens biological changes.